Feature, Structure and Classification of Adhesion Molecules: An Overview - Coombe, Deirdre; Dye, Danielle (Science Publishers, 2010)
Cell adhesion molecules allow cells to communicate with each other and with their environment. The interactions between cell adhesion receptors and their ligands orchestrate the assembly of cells into tissues, organs and systems, and lead to the formation of multicellular organisms. Numerous different adhesive events, which may be synergistic or antagonistic, are required for organizing a tissue or a cell behavior. It is the balance between these events that determines the structure of a tissue, or whether cells stay in tight association with other cells or migrate around the body.There are four main families of cell adhesion receptors: the immunoglobulin superfamily, integrins, cadherins and selectins. The cadherins mediate strong cell-cell adhesion and play a fundamental role in morphogenesis and development, while integrins are critical to cell-matrix interactions and cell migration through the extracellular matrix. Immunoglobulin superfamily members contribute to and modulate cell-cell interactions. These three large families contribute to adhesive interactions between many cell types in different tissues. The selectins have three members and they perform a very specific role critical for leukocyte migration from the vasculature.